Metode Sabaq, Sabqi, dan Manzil, Solusi Menjaga Hafalan al-Qur’an Secara Konsisten - Achmad Tamyiz; Joko Subando (TSAQOFAH, 2026)
Although the Qur’an is the holy book of Muslims whose purity is preserved, efforts to maintain Qur’anic memorization in the practice of tahfizh learning still face challenges related to the need for consistency, discipline, and appropriate repetition methods. This study aims to describe the concept, implementation, as well as the strengths and weaknesses of the sabaq, sabqi, and manzil methods in maintaining Qur’anic memorization consistently. This study used a library research method by examining concepts and practices of tahfizh learning related to strengthening Qur’anic memorization. The results of the review show that the sabaq, sabqi, and manzil methods consist of three main complementary stages, namely sabaq as new memorization, sabqi as repetition of new memorization, and manzil as muraja’ah of previous memorization. These three stages play a role in maintaining a balance between adding new memorization and strengthening memorization that has already been mastered. This method is effective in helping Qur’an memorizers maintain their memorization so that it remains strong (mutqin), fluent, and not easily forgotten, while also fostering discipline, patience, and istiqamah. Thus, the sabaq, sabqi, and manzil methods can serve as relevant tahfizh learning strategies for maintaining Qur’anic memorization sustainably. The implications of this review emphasize the importance of implementing structured repetition methods in the development of Qur’anic memorization in Islamic educational institutions.